Detection of fruit flies (Diptera: Tephritidae) using cue-lure and methyl eugenol in Depok City and Bogor District, West Java, Indonesia - Hagus Tarno; Evy Octavia; Toto Himawan; Yogo Setiawan (Society for Indonesian Biodiversity, 2022)
Abstract. Tarno H, Octavia E, Himawan T, Setiawan Y. 2022. Detection of fruit flies (Diptera: Tephritidae) Using Cue-Lure and Methyl Eugenol in Steiner Traps in Depok City and Bogor District, West Java, Indonesia. Biodiversitas 23: 4202-4208. Fruit flies (Diptera: Tephritidae) are one of the most economically important insect pests worldwide. Two types of attractants are recommended for monitoring and controlling fruit flies: methyl eugenol (ME) and cue-lure (C-L). The objective of this study was to investigate the species richness and abundance of fruit flies (Diptera: Tephritidae) using methyl eugenol (ME) and cue-lure (C-L) in Depok City and Bogor District, West Java, Indonesia. The study was conducted in three sites of fruit orchards in Bogor District i.e., Malay apple (Syzygium malaccense), lemon (Citrus limon), papaya (Carica papaya), and two sites of fruit orchards in Depok City i.e., carambola (Averrhoa carambola) and guavas (Psidium guajava). Male fruit flies were trapped using Steiner traps baited with methyl eugenol (ME) and cue-lure (C-L). There were 11 fruit fly species collected from this study i.e., Bactrocera albistrigata, B. carambolae, B. dorsalis, B. neocognata, B. umbrosa, B. verbascifoliae, Dacus conopsoides, D. longicornis, Zeugodacus calumniata, Z. caudatus, and Z. cucurbitae. In this study, B. albistrigata, D. conopsoides, D. longicornis, and Z. caudatus were only collected in Steiner traps baited with C-L and B. dorsalis, and B. umbrosa also only responded to ME. During sampling periods, 20,217 male adult fruit flies were collected. The highest relative abundance attracted to ME was B. carambolae and C-L was Z. cucurbitae. In this study, B. albistrigata, B. calumniate, D. longicornis, Z. caudatus, and Z. cucurbitae were significantly more attracted to C-L than ME. Whereas, B. carambolae, B. dorsalis, B. umbrosa, and B. verbascifoliae were significantly more attracted to ME than C-L. There were no invasive species in Depok City and Bogor District, West Java, Indonesia. Our study can be used as a method for monitoring and controlling fruit flies, namely Steiner trap with C-L for Z. cucurbitae and Steiner trap with ME for B. carambolae, B. dorsalis, and B. umbrosa in Depok City and Bogor District, West Java, Indonesia.